Hubungan antara Adverse Childhood Experiences dan Regulasi Emosi pada Dewasa Awal di Wilayah Jabotabek - Wiwin Julia; Roswiyani Roswiyani (Lembaga Yasin AlSys, 2026)
Adverse childhood experiences (ACEs) are traumatic events that may have long-term impacts on individuals’ psychological development, including their emotion regulation abilities in adulthood. This study aimed to examine the relationship between adverse childhood experiences and emotion regulation among young adults. A non-experimental quantitative approach with a correlational design was employed. The participants were 375 young adults recruited through purposive sampling. Data were collected online using the Indonesian version of the World Health Organization Adverse Childhood Experiences International Questionnaire (WHO ACE-IQ) to measure adverse childhood experiences and an emotion regulation scale to assess emotion regulation abilities. Data were analyzed using Spearman’s correlation test. The results showed a significant positive relationship between adverse childhood experiences and emotion regulation (r = 0.445; p < 0.001) with a moderate effect size, indicating that the higher the level of adverse childhood experiences, the higher the emotion regulation scores among young adults. These findings suggest that traumatic experiences in childhood are associated with individuals’ emotion regulation patterns in adulthood, highlighting the need for serious attention as well as preventive efforts and early interventions targeting adverse childhood experiences.